Communicating with Teens about Sex: Facts, Findings, and Suggestions - Kate Fogarty; Carolyn H. Wyatt (EDIS, 2006)
FCS-2251, a 4-page illustrated fact sheet by Kate Fogarty and Carolyn H. Wyatt, is one of a series of discussions on understanding teen sexuality. This publication discusses the low percentage of teens who communicate with their parents and provides information about effective communication styles and advice for parents and sexual health educators. Includes references. Published by the UF Department of Family Youth and Community Sciences, October 2006.